Origins of the Pressure-Induced Phase Transition and Metallization in the Halide Perovskite (CH3NH3)PbI3 - Lee, Jung-Hoon; Jaffe, Adam; Lin, Yu; Karunadasa, Hemamala, I; Neaton, Jeffrey B. (AMER CHEMICAL SOC, 2020)
Hybrid halide perovskites are promising for applications because of their favorable optoelectronic properties and low cost. Here we investigate the effects of hydrostatic pressure on the structural and electronic properties of (MA)PbI3 (MA = CH3NH3+) using first-principles density functional theory calculations. Our calculations predict that at a pressure of 0.23 GPa, the orthorhombic Fmmm phase becomes unstable with respect to a cubic Im (3) over bar phase, in good agreement with room-temperature experiments (similar to 0.3 GPa). At higher pressures, about 6 GPa, we predict the onset of pronounced intra- and interoctahedral distortions. This symmetry lowering leads to the introduction of I 5p-I 5p* antibonding and Pb 6p-Pb 6p bonding character into the valence band maximum (VBM) and the conduction band minimum (CBM) states, respectively. We find this change in bond character explains the evolution of the VBM and CBM states under compression, trends that ultimately lead to metallization at significantly higher pressures.
Keywords: DENSITY-FUNCTIONAL THEORY; INDUCED AMORPHIZATION; ENERGY; 3D